The Motion Beyond Sense Towards Cognitive Evolution and Unified Laws of Motion - Peng Fu, Aaron (JOURNAL OF ADVANCES IN PHYSICS, 2020)
This paper first explores the relationship between cognition and motion. Our typical cognitive mode, based on sensory forms, is integrated and, therefore, non-motion in nature. This highlights stability and relativity for practical cognitive needs, but at the same time prevents us from developing cognition of the complete form of motion. The result is a fundamental cognitive barrier for us to understand motion. By discovering the underlying cognitive principles, however, we can revise the cognitive process and redevelop the cognitive mode to meet the purpose of direct cognition of motion. Based on this newly developed cognitive mode, we will learn motion features directly and understand motion laws and principles, to explain natural phenomena and establish wide-range connections between them. These include the underlying principles of motion, gravity, the creation of matter and material forms, universal motion, and spacetime.